Ensino de leitura com uso de software educativo: Novas contribuições - Ponciano, Vera Lúcia de Oliveira (2006)
The problematic one of the failure pertaining to school is current situation for many children and young, being the precariousness of the minimum repertoire of reading one of the great impediments to the good pertaining to school performance. Such precariousness is not exclusive of pupils who are at the beginning of the school years, but is fact also in more advanced series, what it becomes urgent the necessity of researchers to give answers for, at least, to minimize the learning gaps. The paradigm of the equivalence of stimulus has been used, for the analysts of the behavior, in studies on the reading. Such studies present resulted promising for the acquisition and perfectioning of basic repertoires of reading; however, they restrict it the initial repertoire of the pupil, since they work with the education of words. The present work had for objective to implement a proposal of education with use of an educative software (Master ®), oriented in the equivalence paradigm of stimulus, using segments ampler than the words. The research consisted of two studies. Study 1. An instrument of evaluation of the reading repertoire was elaborated, focusing the relations equivalence from phrases, with the objective to evaluate the performance of pupils of 5ª level (Middle School) directed for recovery. Study 2. Two procedures of education had been implemented, whose point in common was the use of phrases. Two groups had been formed, each one of which passed for one of the education procedures. Six pupils had participated, having between 11 and 20 years, that attended Middle School (5ª to 8ª levels), being that one of them presented diagnosis of Syndrome of Down and another one of visual deficiency. The results show that all had gotten satisfactory performances, as much in the trained relations, how much in the tested relations, however in different tests of reading generalization the performance platforms had been differentiated. One, of the four participants who concluded all the stages of the experiment the one that if they had submitted, more than reached 80% of rightnesss in tests of generalization, that estimated the control of minimum units (syllables), in composed phrases for words not trained; although one another has approached this platform. It was verified, still, the maintenance of the performances presented after an interval of 28 days. The gotten data evidence that all the participants had raised its repertoire of reading, reaching superior levels of performance to the produced ones comparedwith the previous years of school. Considering the small number of sessions (in the maximum 17 sessions that had varied between 20 to 40 minutes) the one that the participants if had submitted during the procedure of education and the presented performances one concludes that it has possibility of take itself in the equivalence paradigm of stimulus in education segments ampler than the word and that educative software Mestre®, with the use of phrases, is a valuable resource to teache and perfectioning of the reading